(untitled) (International Journal of Research in Pharmaceutical Sciences and Technology, 2026)
Acne vulgaris is a prevalent inflammatory skin disorder that often requires prolonged topical therapy. Hydrogels are promising drug delivery systems due to their biocompatibility, ease of application, and ability to enhance localized drug delivery. Castor oil, with its antimicrobial and anti-inflammatory properties, was incorporated into a hydrogel to develop a potential topical formulation for acne management. Aim and Objectives: This study aimed to formulate and evaluate a castor oil-loaded hydrogel and investigate its physicochemical characteristics, skin compatibility, and antibacterial activity against acne-causing bacteria. Methodology: The hydrogel was prepared using xanthan gum and gelatin as the polymeric matrix with a suitable crosslinking agent. The optimized formulation was evaluated for organoleptic characteristics, pH, viscosity, texture, homogeneity, and skin irritation. Antibacterial efficacy was determined using the agar diffusion method by comparing the zone of inhibition with standard benzoyl peroxide gel and marketed Sotret® gel. Results: The developed castor oil-loaded hydrogel exhibited desirable physicochemical properties, including a skin-compatible pH, suitable viscosity, good texture, and homogeneous appearance, while showing no signs of skin irritation. The formulation demonstrated antibacterial activity with a zone of inhibition of 12.6 ± 0.11 mm. Although the antibacterial efficacy was lower than that of standard benzoyl peroxide gel (44.3 ± 0.24 mm) and marketed Sotret® gel (38.5 ± 0.19 mm), the hydrogel showed appreciable antibacterial potential. Conclusion: The formulated castor oil-loaded hydrogel exhibited satisfactory physicochemical characteristics, good skin compatibility, and promising antibacterial activity, indicating its potential as a natural topical formulation for acne management. Further studies on stability and in vivo efficacy are warranted to establish its therapeutic potential.